Gender dimensions of non-formal employment in Colombia (2003)
This paper analyzed gender in the informal sector in Colombia, using the urban part of the Encuesta Nacional de Condiciones de Vida 1997, under the hypothesis that many informal women belong to this sector because it is more convenient for their childcare and house care needs. It is found that informal women are less in the lower strata than informal men, have better housing than informal men, and are covered by social security more often. More informal women have a family business in the household and work in their own home more often than informal men and tend to work between 6 and 11 hours less per week than informal men on average. Although fertility increases the woman's and men's probability of being informal, for a woman, having a child who stays with her most of the time during the week, either at home or at work, increases significantly her probability of being informal by 0.22, indicating that childcare contributes more to female than to male informality (for males it is not significant). When fertility is instrumented, this effect is revealed even larger. Models of log hourly wages/earnings were also estimated separately by gender and by sector of employment.